تصور الذات لدى التلاميذ ضحايا التنمر المدرسي - عقاقنية, مهاء; العايب, رابح (جامعة الوادي - University of Eloued, 2023)
جاءت هذه الدراسة الميدانية قصد التعرف على تصور الذات لدى التلاميذ ضحايا التنمر المدرسي، فقد تم الاعتماد على النهج الوصفي التحليلي عبر تطبيق بطاقة التداعي و الاستمارة التميزية لرصد محتوى و بناء تصور الذات لدى عينة من التلاميذ ضحايا هذه الممارسات الهدامة. تم الاستعانة بأساليب تحليل مزجت بين كيفي و كمي مثل التحليل الشبه او حساب التوارد و حساب مؤشرات التنوع و الندرة قصد تبويب و تنظيم التداعيات المنتجة و الوصول إلى تمثل واضح للبناء النفسي. خلصت الدراسة إلى أن تصور الذات مبني بطريقة منظمة و مستقلة غير انه يحمل معاني و دلالات سلبية تم ترسيخها عبر الممارسات العدوانية التي تعرض لها هؤلاء التلاميذ. فالتكوين المركزي و المحيطي للتصور محمل بالآثار النفسية العميقة للظاهرة، غير أن الرغبة في التغير و النجاح واضح أيضا في التداعيات المنتجة و يعبر على الأمل في تحسين الحياة. Abstract: This field study was aimed at identifying the self-perception of students who are victims of school bullying. The descriptive analytical approach was relied upon by applying the association card and the discriminatory questionnaire to monitor the content and build the self-perception of a sample of students who are victims of these destructive practices. Analysis methods that mixed qualitative and quantitative methods were used, such as qualitative analysis and calculating indicators of diversity and scarcity, in order to classify and organize the productive repercussions and reach a clear representation of the psychological structure. The study concluded that the self-perception is built in an organized and independent manner, but it carries negative meanings and connotations that were consolidated through the aggressive practices that these students were subjected to. The central and peripheral formation of the perception is loaded with the profound psychological effects of the phenomenon.
مقال
Keywords: التصور الذات؛ التنمر المدرسي؛ العناصر المركزية؛ العناصر المحيطية; self-perception; school bullying; central elements; peripheral elements